2007
DOI: 10.1109/imtc.2007.379353
|View full text |Cite
|
Sign up to set email alerts
|

Bending Curve Modeling of Ionic Polymer Metal Composites in Soft Actuator Applications

Abstract: Ionic Polymer Metal Composites (IPMC) may be used to replace the electro-mechanical actuators in a vast variety of application areas rangingfrom biomedical devices to soft actuators and sensor systems in modern humanoid robotics. The excellent characteristics shown by IPMCs are highly influenced by their interrelated mechanical, electrical and chemical properties. However, this makes it complicated and difficult to understand the physics and predict their behavior. In order to utilize the full potentials towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…(5) The resulting strain distribution varies linearly along the thickness of the actuator with respect to the distance from the neutral axis (Alici et al, 2006;Samaranayake et al, 2007), as shown in Figure 10.…”
Section: Electromechanical Modelingmentioning
confidence: 99%
“…(5) The resulting strain distribution varies linearly along the thickness of the actuator with respect to the distance from the neutral axis (Alici et al, 2006;Samaranayake et al, 2007), as shown in Figure 10.…”
Section: Electromechanical Modelingmentioning
confidence: 99%
“…Their inherent light weight, flexibility, repeatability and the tip force have been the major concerns to replace the electro-mechanical actuators in a vast variety of afore mentioned application areas. Many studies have been carried out to develop cost effective fabrication techniques, improve electro-chemo-mechanical characteristics, derive finite element and other modeling techniques, etc [2]. However very little attentions have been paid on the control of IPMCs.…”
Section: Introductionmentioning
confidence: 99%
“…It is neutralized with the necessary amount of counter-ions such as H+, Li+, Na+, K+ etc, balancing the charge of anions covalently fixed to the backbone membrane. When a thin strip of an IPMC membrane in the hydrated state is stimulated by the application of a step voltage, the composite bends towards the anode [2]. The magnitude and speed of these deflections depend on the nature of the counter-ions, the structure of the electrodes, the level of hydration (solvent saturation), etc [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation